Você está na página 1de 48

n

i P (i) P (i) P (i)

P (i) 0

i

P (i) = 1

P (i) = 0 P (i) = 1 1 i j

P (i j) = P (i) + P (j)

P ( i) = 1 P (i)

P (i) = 1/6

3 6

P (3 6) = 1/6 + 1/6 = 1/3

i

j

P (i j) = P (i)P (j)

P (1, 8) = 1/10.

P (m) = 1/2. P ( + 1, 8 m) = P (m)P (1, 8) = 1 2 ×

1, 8 m

P (m + ) = P (m)P ( ) =

730

1 1

10

=

20

1

2 ×

1

365 =

1

E 1 E 2 E 1 E 2

P(E 1 ) > P(E 2 )

P (E)

P (E) P (i) = 1/n i n P ( ) = P ( ) = 1/2 P (E) N P (i) i

P (i) =

lim

N →∞

N i

N

N i i N P (E) P (E) E I P (E|I).

E 1 E 2 P 1 P 2 P 1 = P 2 = 1/2 P 1 = 1/5 P 2 = 4/5 P 1 = P 2 = P 3 = P 4 = 1/4

P 1 = P 2 = P 3 = P 4 = P 5 = P 6 = 1/6

S(P 1 , P 2 ,

P i i

P 1 = P 2 =

= 1/

,

P i ,

)

= P i =

S(1/, 1/,

) = S(Ω)

S(Ω)

Ω = 1

S(Ω = 1) = 0

S(Ω 1 ) > S(Ω 2 ) 1 > 2

S

1 2

1 2 .

S

S(Ω 1 2 ) = S(Ω 1 ) + S(Ω 2 )

S

S(xy) = S(x) + S(y)

x, y

z = xy S

∂S(z)

∂z S(z)

 

=

= y S(z) z

∂x

∂x

z

∂S(z)

∂z S(z)

 

=

= x S(z) z

∂y

∂y

z

 

∂S(z)

∂x

∂S(z)

∂y

= S(x) x

S(y)

=

y

S(x)

x

S(y)

y

=

=

y S(z) z

x S(z) z

x y

x S(x) x

=

y S(y) y

= z S(z) z

x

y x y

x S(x) x

=

y S(y) y

= A

S(x) = A x + B

A A = 1 S

B

S(Ω) =

S = P i P i

i

S

P i =

1

i

= = Ω Ω =

1

1

1

i

j P j = 1 P i = 0

i

= j S = 1 1 = 0

S

S

P i

P 1 ( ) = P 2 ( ) = 1/2

P 1 + P 2 = 1 S

S

= P i P i = (P 1 P 1 + P 2 P 2 )

i

= [P 1 P 1 + (1

P 1 ) (1 P 1 )]

=

S

P 1

P 1

1 P 1

=P 1

=

=

=

[ P 1 + 1 (1 P 1 ) 1] =

1

1

2

P 1

1 P 1

= 0

2 S

2

P

1

=

1

1

P 1 = 4 < 0

P

1

1

+

E 1 E 2 E 3 1 2 3

f = 1, 9

P 1 P 2 P 3

f = 1, 9

P (1), P (2),

x

x =< x >

, P (n) n

x

x 1 P (1) + x 2 P (2) +

=

n

i=1

x i P (i)

+

x n P(n)

f (x) x

f(x) =

n

i=1

f(x i )P (i)

f (x) + g(x) = f (x) + g(x)

cf (x) = cf (x)

f g x c

P

x m

f (x) = x m

n

i=1

x m P (i)

i

x

x x x

x ∆ x ≡ x − x ∆ x = ( x − x ) =

x = (x x) = x x = 0

j P (i) = 1, i = j

x 2

(x x) 2

=

(x 2 2xx + x 2 )

=

x 2 2xx + x 2

=

x 2 − x 2

x 2 x 2

m

x m = (x x) m

p q

p = 1/2 q = 1 p = 1/2

N n

N

µ B

B/| B| = zˆ

E = µB

E = sµB s = ±1

s

µ B =

e /2m e E = g s µ B s · B g s 2

1

s = ± 2 zˆ

p +1 q 1 p+q = 1 p = q = 1/2 N M

M = µ(s 1 + s 2 +

+ s N ) = µ

N

i=1

s i

N l t p q = 1 p N n n n + n = N

P N (n) n P N (n)

P N (n) = W N (n, n )p n q n

W N (n, n ) N n n n n N = 2 N = 16 W N W N1 n n N N 1 (n 1) n n (n 1) W N (n 1, n ) W N1 (n, n 1)

W N (n, n ) = W N1 (n 1, n ) + W N1 (n, n 1)

W 0 (0, 0) = 0 W 1 (1, 0) = W 1 (0, 1) = 1 W N (n, n ) N

W 2 (2,

0)

=

W 1 (1,

0) +

W 1 (2, 1) = 1 + 0 = 1

W 2 (1,

1)

=

W 1 (0,

1) + W 1 (1, 0) = 1 + 1 = 2

 

W 2 (0, 2) = W 1 (1, 2) + W 1 (0, 2) = 0 + 1 = 1

N esima´

W N (n, n ), W N (N, 0)

W N (0, N )

W N (0 , N ) W N ( n, n ) N − esima ´

W N (n, n ) N esima´ W N (n, n ), W N (N, 0) W N (0, N )

W N (n, n ) =

N!

n!n ! =

N!

n!(N n)!

0! = 1 P N (n)

P N (n) =

N! n)! p n q (Nn) n!(N

p = q = 1/2

P N (n) =

N! n)! 2 N

n!(N

N 2 N

1/2 N N

N

N 1 N 2

N !

n N

N 1 N n + 1

n n n N

A

n

N =

N!

(N n)!

n

N n

n N C N

A n N C N

n

n

n

A n N = C N n!

n

n N!

N =

C

n!(N n)!

n N

(x + y) N

=

=

1

x N + Nx N1 y + 2 N (N 1)x N2 y 2 +

N

n=0

N!

n!(N n)! x Nn y n

x = y = 1

N

n=0

C N = 2 N

n

+

N! n)! x Nn y n +

n!(N

+

y N

W N (n, n )

(p + q) N =

p + q = 1

N

n=0

N!

n!(N n)! p n q Nn = 1

N = 20, 40, 60, 80, 100 p = 0, 5 0, 7

P N ( n ) n n/n N = 20( ) , 40( ) ,
P N ( n ) n n/n N = 20( ) , 40( ) ,
P N ( n ) n n/n N = 20( ) , 40( ) ,

P N (n)

n n/n N = 20( ), 40( ), 60( ), 80( ), 100( ) p = 0, 5 0, 7

p = 0, 5

N

N n/n

N P N (n) N

p = 0, 7

n/n

p = 0, 5 p = 0, 7

P N (n)

n

n =

N

n=0

nP N (n) =

N

n=0

n

N!

n!(N n)! p n q Nn

p

p p n = np n

n

=

N

n=0

N! n!(N n)! (p

∂p p n )q Nn

= p

∂p

N

n=0

n!(N n)! p n q Nn

N!

=

p p (p + q) N

= pN (p + q) N1

= pN

n = qN = (1 p)N

n

2

(p + q) = 1

=

=

= (

=

=

=

N

n=0

N

n=0

n

2

N!

n!(N n)! p n q Nn

N! n!(N n)! (p

∂p ) 2 p n q Nn

p

∂p ) 2

N

n=0

n!(N n)! p n q Nn

N!

(p p ) 2 (p + q) N

p p pN (p + q) N1

p N(p + q) N1 + pN (N 1)(p + q) N2

n 2

=

p [N + pN (N 1)]

=

p pN 2 + N (1 p)

=

(pN ) 2 + p(1 p)N

=

n 2 + pqN

2

= ( pN ) 2 + p (1 − p ) N = n 2 +

σ n = (∆n) 2 = n 2 n 2 = pqN

σ n = pq N

N σ n /n

σ n = √ pqN n pN
σ n
= √ pqN
n pN

=

p 1/2 1

q

N

N

n

n N σ n N

σ n /n 1/ N n p σ n = 0, 5 N

σ n /n = 1/ N p = 0, 5

= 0, 655/ N p = 0, 7 σ n σ n /n p = 0, 7

p = 0, 5

p = 0, 5 σ n = 0, 458 N

p = 0, 7

N N

x

RandomW alk1D

p

q

p

N

x = n n < x 2 >

x = n − n < x 2 > RandomW alk 1 D N = 4
x = n − n < x 2 > RandomW alk 1 D N = 4
x = n − n < x 2 > RandomW alk 1 D N = 4
x = n − n < x 2 > RandomW alk 1 D N = 4
x = n − n < x 2 > RandomW alk 1 D N = 4
x = n − n < x 2 > RandomW alk 1 D N = 4
x = n − n < x 2 > RandomW alk 1 D N = 4
x = n − n < x 2 > RandomW alk 1 D N = 4
x = n − n < x 2 > RandomW alk 1 D N = 4

RandomW alk1D N = 4, 16, 32 10, 50, 100, 1000

N x p N N N

N

31 32.000

128.000 stp RandomW alk2D

N N n ˜ P N ( n ) P N n ˜ N 1

N

N

n˜ P N (n) P N n˜ N 1

P N

P N × n

P N = A + B(n n) 2 A B

P N n N = 60 P N n = n ˜ P N (

P N n N = 60

P N

n = n˜

P N (n) = P N (n = n˜) + (n n˜) P n N (n)

| nn +

1 (n n˜) 2 2 P N (n)

2

n 2

| n=˜n +

A

=

P N (n = n˜)

2 P N (n)

B n 2

=

| n=˜n

P N (n) A

2 1 B(n n˜) 2

P N (n) Ae

1

2 B(nn˜) 2

N ! N

1

N ! N N N + 2 (2πN )

n! c nn n /e n

c = 2π

N

N ! N N N

 

n! = ˆ x e x x n

0

ˆ

0

x e x x n = ˆ (e x ) x n = x n e x | x= + n ˆ

0

x=0

0

=

n ˆ x e x x n1

0

f(x) = x n e x

x e x x n1

x n x e x

f (x) x 0

f

=

[ f (x)]

x

x (n x x)

=

=

x 0 = n

0

n

x 1 = 0

x = n + ξ

f n (ξ) = n (n + ξ) (n + ξ)

(n + ξ)

=

ln n + ln 1 +

ln n +

n

ξ

n 1 n 2 +

ξ

ξ

2

2

ln x

=

=

(x 1) + 1

2 (x 1) 2 + 3 (x 1) 3 +

1

n=1

1

(1) n1 n (x 1) n 0 < x 2)

ln f n (ξ) n ln n n 1

ξ

2

2 n

f n (ξ) n n e n e ξ 2 /2n

f n (x) x f n (ξ) ξ

x [0, ] −→ ξ [n, ]

n! ˆ

n

ξ n n e n e ξ 2 /2n

f n (ξ) ξ < n

−∞

n! n n e n ˆ

−∞

ξ e ξ 2 /2n

=

n n e n 2πn

N > 5 N > 50

P N (n) = N ! n! (N n)! + n p + (N n) p

( P N (n))

n

= n + (N n) + p q

n n˜ P N (n)/ n = 0

N n˜

n˜

= q

p

(p + q) = 1

(N n˜)p

=Np

=

=

nq˜

n˜(p + q) = n˜

n˜ = n n P N (n)

B

2 ( P N (n))

n 2

1

= n

1

N n

B =

2 ( P N (n)) n 2

| nn =

1

1

n˜ + N n˜ =

N

= (Np)N (1 p) =

1

Npq

B =

1

2

σ n

N

n˜(N n˜)

A,

n = n˜ n˜ = pN

A

=

=

=

=

=

=A

=

P N n) = N ! n˜! (